Offensive waste valorisation in the UK: Assessment of the potentials for absorbent hygiene product (AHP) recycling. (1st April 2019) - Takaya, C.A.; Cooper, I.; Berg, M.; Carpenter, J.; Muir, R.; Brittle, S.; Sarker, Dipak K.
Highlights: AHPs and plastics are the main wastes in the offensive human waste bags sampled. Recycled AHPs are potential feedstocks for bio-composite and fertilizer industries. Superabsorbent polymer and pulp recyclate quality play key roles in processing viability. Abstract: Offensive human waste refers to non-hazardous waste that contains body fluids from non-infectious humans, comprised of post-consumer Absorbent Hygiene Products (AHPs), swabs, dressings, bedding, gloves, and other materials. While this waste category requires more stringent handling, storage and disposal measures than general waste, its non-hazardous nature suggests that there are opportunities for waste valorisation. An inventory of 200 offensive human waste bags collected from various healthcare institutions in South-Eastern England show that about 76% of the waste is comprised of AHPs, most of which are adult incontinence pads and child nappies. Mixed plastics comprised of predominantly HDPE represent 9% of the waste. To evaluate the potentials for offensive human waste valorisation, small-scale separation tests involving artificially-soiled nappies and associated mixed plastic packaging wastes have been performed. Findings suggest that about 50% of the total superabsorbent polymer is recoverable from fluff pulp fractions, recoveries of which are unaffected by the presence of ionic species typically present in human waste. On the other hand, recovery of mixed plastic packaging is more challenging. Overall, however, findings suggest that viable AHP recycling is possible if recyclate materials are targeted towards non-food related markets outlets such as the construction and land remediation sectors.